Challenges for Annotation Concepts in Music. Issue 2 (October 2017) - Hadjakos, Aristotelis; Iffland, Joachim; Keil, Reinhard; Oberhoff, Andreas; Veit, Joachim
Abstract : Traditional historico-critical music editions provide scholars and musicians with an edited score based on the interpretation of various sources such as the composer's autograph(s), letters and other materials from copyists or publishers. Their digital counterparts have the potential to offer new and more expanded ways to explore the work. This is based on the possibility to provide large amounts of source materials and to annotate more extensively (since printing costs are irrelevant). Furthermore, audio and video recordings of performances can be integrated. But, similarly important, the user interface makes it much easier to navigate in the complex network of cross-references between various source materials and the editor's annotations. The XML-based Music Encoding Initiative (MEI) format is the standard music representation format for digital music editions. In this article we discuss current MEI-based annotation practices and outline the current challenges for music annotations, including a discussion of anchoring options, the embedding of addressable elements in the local musical context, the annotation of audio, and the categorisation of annotations. This leads to a discussion of open questions such as the ability to secure authorship in open and reusable editions.